2011
DOI: 10.1002/gps.2680
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of behavioural therapy for the treatment of depression in older adults: a meta‐analysis

Abstract: Behavioural therapy in depressed older adults appears to have comparable effectiveness with alternative psychotherapies. Further research is recommended with the need for larger sample sizes, more clarity on trial design and the intervention, longer term follow-up and concomitant economic evaluations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 43 publications
0
48
0
5
Order By: Relevance
“…68 The results of the CASPER trial therefore add to an emerging evidence base that behavioural activation is effective for older adults. 69 The results of the economic evaluation provide robust evidence relating to the cost-effectiveness of collaborative care for people with lower-severity depression. The CASPER trial provides estimates of the overall costs of the intervention, which will be useful for those who might plan services.…”
Section: Discussion Of the Main Findingsmentioning
confidence: 99%
“…68 The results of the CASPER trial therefore add to an emerging evidence base that behavioural activation is effective for older adults. 69 The results of the economic evaluation provide robust evidence relating to the cost-effectiveness of collaborative care for people with lower-severity depression. The CASPER trial provides estimates of the overall costs of the intervention, which will be useful for those who might plan services.…”
Section: Discussion Of the Main Findingsmentioning
confidence: 99%
“…72 The results of the CASPER plus trial, therefore, add to an emerging evidence base that behavioural activation is effective for older adults. 73 The results of the economic evaluation provide robust evidence relating to cost-effectiveness of collaborative care for older people with depression. The CASPER plus trial provides estimates of the overall costs of the intervention, which will be useful for those who may plan services.…”
Section: Doi: 103310/hta21670mentioning
confidence: 99%
“…In a recent systematic review, a meta-analysis showed that, compared with waiting list, group cognitive behavioural therapy is an effective intervention for reducing depressive symptoms in older adults with sub-threshold depression (Krishna et al, 2013). However, major limitations of these studies were the inclusion of non-randomised studies (Samad et al, 2011) and broadly defined interventions (e.g. psychotherapy) (Cuijpers et al, 2006;Peng et al, 2009;Wilson et al, 2008).…”
Section: Resultsmentioning
confidence: 97%
“…The effectiveness of cognitive behavioural therapy for older people Reviews and meta-analyses of the voluminous literature on CBT outcome studies have concluded that CBT is a highly effective approach for the treatment of depression (Gaffan et al, 1995;Oei & Dingle, 2008;Samad et al, 2011). Most Clinical Practice Guidelines advocate the additional benefit of supporting antidepressant medication with CBT (National Institute for Clinical Excellence, 2009).…”
Section: Resultsmentioning
confidence: 98%